2006
DOI: 10.1096/fj.05-4540fje
|View full text |Cite
|
Sign up to set email alerts
|

A sulfated disaccharide derived from chondroitin sulfate proteoglycan protects against inflammation‐associated neurodegeneration

Abstract: Chondroitin sulfate proteoglycan (CSPG), a matrix protein that occurs naturally in the central nervous system (CNS), is considered to be a major inhibitor of axonal regeneration and is known to participate in activation of the inflammatory response. The degradation of CSPG by a specific enzyme, chondroitinase ABC, promotes repair. We postulated that a disaccharidic degradation product of this glycoprotein (CSPG-DS), generated following such degradation, participates in the modulation of the inflammatory respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
58
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 88 publications
(65 citation statements)
references
References 88 publications
4
58
0
3
Order By: Relevance
“…Effective knockout of PTPσ using lentiviral delivery of small interfering RNAs also led to motor and sensory recovery along with neurite outgrowth (68). However, it has also been shown that the products of CSPG enzymatic digestion encourage neurite outgrowth and have an immunomodulatory role in inflammatory central nervous system lesions (69,70). Therefore, targeting a specific CSPG receptor such as PTPσ, may not produce all the beneficial effects of ChABC.…”
Section: Discussionmentioning
confidence: 99%
“…Effective knockout of PTPσ using lentiviral delivery of small interfering RNAs also led to motor and sensory recovery along with neurite outgrowth (68). However, it has also been shown that the products of CSPG enzymatic digestion encourage neurite outgrowth and have an immunomodulatory role in inflammatory central nervous system lesions (69,70). Therefore, targeting a specific CSPG receptor such as PTPσ, may not produce all the beneficial effects of ChABC.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, functional recovery was not observed until at least 6 weeks post-SCI, probably because axons retracted from the lesion site after injury, and outgrowth was not initiated until CSPG digestion rendered the substrate permissive to axon growth. Moreover, the effects of chABC may partially be due to antiinflammatory and neuroprotective effects of the soluble disaccharidic end products of chABC-mediated digestion of CSPG (39,40).…”
Section: Discussionmentioning
confidence: 99%
“…One mechanism by which microglial cell activation is reduced after cABC infusion is by the cABC cleavage of CSPGs to a disaccharidic degradation product that has previously been shown to markedly reduce T-cell infiltration and microglial activation after experimental autoimmune encephalomyelitis. 57 Clearly, cABC has a multitude of effects in the brain, in addition to the well-studied sprouting response, that have only just begun to be unraveled.…”
Section: And (E) Gap43mentioning
confidence: 99%